New trends in information and communications technology applications : third International Conference, NTICT 2018, Baghdad, Iraq, October 2-4, 2018, Proceedings /: third International Conference, NTICT 2018, Baghdad, Iraq, October 2-4, 2018, Proceedings. (2018) - Unknown
No abstract available